ASSESSING THE POTENTIAL DEMAND FOR AUTONOMOUS SHUTTLE BUSES AT UUM: A STUDY ON TECHNOLOGY ACCEPTANCE FOR STUDENT PERSPECTIVE (Journal of Technology and Operations Management, 2025)
Autonomous vehicles (AVs), particularly autonomous shuttle buses, are emerging as sustainable and cost-effective transportation solutions, with the potential to reduce travel costs by 6%–11%. At Universiti Utara Malaysia (UUM), the current shuttle service is plagued by overcrowding, delays, and inconsistent driver behavior, negatively affecting the student commuting experience. Despite the potential advantages of AVs, user acceptance remains limited due to concerns about safety, trust, and system reliability—especially in unfamiliar settings. This study aims to assess the potential demand for autonomous shuttle buses among UUM students, focusing on four key determinants: perceived usefulness, perceived ease of use, trust, and safety. Data were collected from 380 student respondents and analyzed using IBM SPSS software for descriptive statistics, correlation, and regression analysis. The findings reveal that perceived ease of use, trust, and safety significantly influence the intention to use autonomous shuttle buses. However, perceived usefulness, while positively associated, does not have a statistically significant impact on demand, suggesting that students are more influenced by functional reliability and confidence in the system. These results offer valuable insights for universities and transport technology developers. To ensure successful implementation, initiatives should prioritize trust-building, system safety, and user-friendly designs to support the adoption of autonomous mobility in campus environments.